2020
DOI: 10.3389/fnhum.2020.00308
|View full text |Cite
|
Sign up to set email alerts
|

The Benefit of Cross-Modal Reorganization on Speech Perception in Pediatric Cochlear Implant Recipients Revealed Using Functional Near-Infrared Spectroscopy

Abstract: Cochlear implants (CIs) are the most successful treatment for severe-to-profound deafness in children. However, speech outcomes with a CI often lag behind those of normally-hearing children. Some authors have attributed these deficits to the takeover of the auditory temporal cortex by vision following deafness, which has prompted some clinicians to discourage the rehabilitation of pediatric CI recipients using visual speech. We studied this cross-modal activity in the temporal cortex, along with responses to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 97 publications
(167 reference statements)
3
47
0
Order By: Relevance
“…An alternative approach to account for differences between the model and the measured response is to include a derivative term in the design matrix. 13 , 75 However, since we observed good correspondence between the response morphology and the expected canonical response, we did not include derivative terms in our analysis. The response morphology, and appropriate boxcar length, may vary with stimulus duration, characteristics, and brain structure of interest.…”
Section: Resultsmentioning
confidence: 99%
“…An alternative approach to account for differences between the model and the measured response is to include a derivative term in the design matrix. 13 , 75 However, since we observed good correspondence between the response morphology and the expected canonical response, we did not include derivative terms in our analysis. The response morphology, and appropriate boxcar length, may vary with stimulus duration, characteristics, and brain structure of interest.…”
Section: Resultsmentioning
confidence: 99%
“…There have also been several fNIRS studies that have been conducted involving adults and children with CIs [77][78][79][80]. This work with CI users demonstrated levels of cross-modal plasticity [78,80], overlap in the processing of the features of auditory speech between CI users and normally hearing children [78], and an overall neurotypical pattern of activation during auditory language tasks [77]. Crucially, all of this work has demonstrated the utility and tolerability of this technique for studies with CI-users.…”
Section: Introductionmentioning
confidence: 74%
“…Three records reported studies from the UK [78,86,87], three reported studies from Germany [88][89][90], one reported a study from the US [91], and one study was from Australia [92]. All of the included studies were published between 2016 and 2020.…”
Section: Characteristics Of Sources Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…According to fNIRS analyses, newborns consistently exhibit a strong hemodynamic response to universally preferred syllables, which suggests that the early acquisition and perception of language can be detected using categorical linguistic sounds (Gomez et al, 2014 ). The applications of this technology have the potential to provide feedback for speech therapy or in the tuning of hearing aid devices (e.g., cochlear implants) at an early stage of development based on brain recordings (Mushtaq et al, 2020 ). Several groups have demonstrated fNIRS use for measuring brain responses in deaf children with cochlear implants (Sevy et al, 2010 ; Pollonini et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%